2014
DOI: 10.2147/ndt.s47790
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping well with cancer: a systematic review of cognitive behavioral therapy for insomnia in cancer patients

Abstract: Individuals with cancer are disproportionately affected by sleep disturbance and insomnia relative to the general population. These problems can be a consequence of the psychological, behavioral, and physical effects of a cancer diagnosis and treatment. Insomnia often persists for years and, when combined with already high levels of cancer-related distress, may place cancer survivors at a higher risk of future physical and mental health problems and poorer quality of life. The recommended first-line treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 94 publications
4
72
0
2
Order By: Relevance
“…As shown by our SEM analyses, the reduction in insomnia severity was directly responsible for improving cancer-related fatigue. These findings are consistent with previous studies that have also shown CBT-I to result in decreased levels of cancer-related fatigue [20,21] and support the use of CBT-I as an effective intervention for fatigue related to cancer in survivors who also have insomnia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As shown by our SEM analyses, the reduction in insomnia severity was directly responsible for improving cancer-related fatigue. These findings are consistent with previous studies that have also shown CBT-I to result in decreased levels of cancer-related fatigue [20,21] and support the use of CBT-I as an effective intervention for fatigue related to cancer in survivors who also have insomnia.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to treating insomnia, CBT-I has also been shown to decrease levels of anxiety and depression related to cancer treatment [20,21]. However, studies examining the efficacy of CBT-I for improving CRF in cancer survivors are conflicting; hence, it is not clear whether the use of sleep management interventions will actually improve CRF [15].…”
Section: Introductionmentioning
confidence: 99%
“…Three randomised controlled trials (RCT) investigating the effect of CBT on insomnia included men with prostate cancer. Of these, Garland et al included 8 men with prostate cancer (7% of total) [59] and Ritterband et al included 4 men [60] , but the cancer site was not identified and neither trial presented results specifically for men with prostate cancer. One RCT encompassed 150 patients with cancer at mixed sites including men with prostate cancer (N = 34; 23%) suffering from insomnia for at least 6 months [53] .…”
Section: Management Of Insomnia Among Men With Prostate Cancermentioning
confidence: 99%
“…A systematic review of these studies concluded that CBT-I is effective in this context with one study showing large effect sizes for sleep latency (SL), wake after sleep onset (WASO), and sleep efficiency (SE). 19 …”
Section: Introductionmentioning
confidence: 99%